Simultaneous Occurrence of Nasal Carcinoma Induced by Enzootic Nasal Tumour Virus-2 (ENTV-2) and Border Disease Virus in Three Goats - Incili, Canan Akdeniz; Eroksuz, Yesari; Timurkan, Mehmet Ozkan; Karabulut, Burak; Yerlikaya, Zeynep; Eroksuz, Hatice (Wiley, 2025)
BackgroundEnzootic nasal adenocarcinoma (ENA) is a prevalent neoplastic disease affecting small ruminant populations globally, caused by the enzootic nasal tumour virus (ENTV). Border disease (BD), also affecting small ruminants, causes persistent infection and increases secondary infection risks.MethodsPost-necropsy tissue samples were routinely processed and stained with haematoxylin and eosin. Histopathological, immunohistochemical and PCR techniques were employed to diagnose ENTV-2 in three goats. Viral RNA extraction and reverse transcription were performed using the WizPrep Viral DNA/RNA micro kit. PCR analysis targeted ENTV-1, ENTV-2 and BD virus (BDV).ResultsENTV-2-induced nasal carcinoma and BDV were identified in three goats from an Eastern Turkey breeding facility. Post-mortem examinations revealed neoplastic growths originating from the ethmoid region and extending throughout the nasal cavity. PCR analysis revealed the presence of both ENTV-2 and BDV genomes in all three cases. Histopathological examination showed invasive acinar and papillary proliferations with multifocal necrosis and lymphohistiocytic infiltrations. Immunohistochemical analysis demonstrated positive reactivity for ENTV in neoplastic cells using a monoclonal antibody specific to the JSRV capsid protein, which also cross-reacts with the envelope protein of ENTV-1.ConclusionThe chronic, immune-tolerant nature of BD infection may have immunosuppressive effects that potentially enhance the impact of ENTV. The simultaneous presence of these two pathogens could synergistically increase the risk of morbidity and mortality in caprine populations.
Keywords: border disease virus; enzootic nasal tumour virus-2; histopathology; immunohistochemistry; PCR